2014
DOI: 10.1111/jai.12489
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses and intestinal morphology of striped catfish, Pangasianodon hypophthalmus (Sauvage, 1878), fed dietary nucleotides

Abstract: Summary The present study was conducted to evaluate the effects of dietary nucleotides (NT) on growth performance, immune responses, and intestinal morphology of striped catfish, Pangasianodon hypophthalmus. Different levels of NT (0, 0.25. 0.5, 0.75, and 1% weight per weight, WW−1) were used in the basal diet and then randomly allocated to triplicate groups of fish with an average initial weight of 1.52 ± 0.11 g for 10 weeks. Nucleotide supplementation did not improve growth parameters significantly (P > 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…observations of the present study were marginally comparable with the earlier report of 90-134 mg dl À1 glucose and 84.1 ± 14.1 ng ml À1 cortisol level in P. hypophthalmus byYaghobi et al (2015) andNguyen et al (2021), respectively. The SOD assay and CAT are oxidative enzymes that influence the homeostasis in cells and are the key factors in animal defence against oxidative stress(Nuwansi et al, 2021).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…observations of the present study were marginally comparable with the earlier report of 90-134 mg dl À1 glucose and 84.1 ± 14.1 ng ml À1 cortisol level in P. hypophthalmus byYaghobi et al (2015) andNguyen et al (2021), respectively. The SOD assay and CAT are oxidative enzymes that influence the homeostasis in cells and are the key factors in animal defence against oxidative stress(Nuwansi et al, 2021).…”
supporting
confidence: 91%
“…The observations of the present study were marginally comparable with the earlier report of 90–134 mg dl −1 glucose and 84.1 ± 14.1 ng ml −1 cortisol level in P. hypophthalmus by Yaghobi et al . (2015) and Nguyen et al . (2021), respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The gastrointestinal (GI) tract in fish is a multifunctional organ, where the complex microbial community interacts with the external as well as internal environment influencing health and disease (Ringø et al 2016). Several studies have described that the gut microbiota in fish has specific metabolic, trophic, and protective functions (e.g., Yaghobi et al 2014, Liu et al 2016. Comprehensive investigations during the last two decades have the enzymatic potential of the commensal microorganisms within the GI tract of fish (Ray et al 2012, Wang et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported Optimun® increased health and growth performance of rainbow trout (Tahmasebi-Kohyani et al, 2011, and striped bass (Li et al, 2015) at low dose administration around 0.15 % to 0.2 % in diet, while the use of higher doses was found to be effective in Black tiger shrimp (Penaeus monodon Fabricius, 1798) with the optimal dose at 0.56 % (Huu et al, 2012). The optimal dose of Optimun® for beluga sturgeon (H. huso) was found around 0.25 % to 0.35 % (Yousefi et al, 2012), while the best dose for striped catfish (Pangasianodon hypophthalmus Sauvage, 1878) was 0.25 % to 0.5 % (Yaghobi et al, 2015). The size of fish could influence the effect of dietary nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the feeding regime implemented, both short and long periods of dietary nucleotides administrations have been reported to have positive effect on fish growth and immunity. Some experiments were conducted over short periods of time, such as 4 wk or less (Guo et al, 2017;Reda et al, 2018), but others, fed the fish with nucleotide diets for 10 wk or more (Shiau et al, 2015;Yaghobi et al, 2015). However, some researchers reported that prolonged administration of nucleotide-supplemented diets led to immune response suppression which negatively impacted the health of the fish.…”
Section: Discussionmentioning
confidence: 99%